Activist ecologies of study in the learning city: deformalisations of educational life. Issue 5 (3rd September 2022) - Rousell, David; Chan, Kelly Ka-lai
ABSTRACT: The combined impacts of COVID-19 and global climate change are destabilising the infrastructures and future prospects of formal educational systems, with schools and universities struggling to adapt to conditions of radical precarity. At the same time, activist movements are generating alter-educational platforms that reappropriate the learning infrastructures of cities as mobile architectures of pedagogical resistance. Building on Harney and Moten's The Undercommons, this paper discusses transnational examples of radical pedagogies that engage the city as an ecology of deformalised study. We highlight examples from Melbourne's COVID-19 lockdown regime, emphasising how informal study enabled community-led responses to crisis at city-scale. We then turn to urban ecologies of study arising from contemporary activist movements, drawing connections between protest movements in Hong Kong and Deleuze and Guattari's concept of the 'war machine'. This leads to a speculative re-imagining of alternative educational values and futures within a milieu of activist study, care, and resistance.